2021
DOI: 10.1192/j.eurpsy.2021.17
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation, mental health, and use of digital interventions in youth during the COVID-19 pandemic: A nationally representative survey

Abstract: Background Public health measures to curb SARS-CoV-2 transmission rates may have negative psychosocial consequences in youth. Digital interventions may help to mitigate these effects. We investigated the associations between social isolation, COVID-19-related cognitive preoccupation, worries, and anxiety, objective social risk indicators, and psychological distress, as well as use of, and attitude toward, mobile health (mHealth) interventions in youth. Methods Data were collected as part of the “Mental Healt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 57 publications
2
57
1
1
Order By: Relevance
“…Ecological translation of compassionfocused intervention components to individuals' daily life through an EMI offers new avenues for tangible, indicated prevention strategies delivering real-world and real-time interventions that are easy accessible by youth [116]. In fact, findings from a recent, nationally representative survey suggest that psychological distress, social isolation, lack of company, and worrying during the COVID-19 pandemic were highly prevalent in youth and, interestingly, associated with the current use of, and a positive attitude toward, digital interventions [33]. the current study, we use EMA items that have been previously used and validated to measure moment-to-moment variation in stress/negative affect, with considerable within-person variability having been observed for these items in several EMA studies [43,95,121] , interindividual differences in within-person variability as well as general response tendencies may influence the number of triggered EMI tasks and, hence, further research is needed to optimize and personalize the assignment of EMI components, e.g., by using methods of artificial intelligence, recurrent neural networks (RNNs) in particular [122].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ecological translation of compassionfocused intervention components to individuals' daily life through an EMI offers new avenues for tangible, indicated prevention strategies delivering real-world and real-time interventions that are easy accessible by youth [116]. In fact, findings from a recent, nationally representative survey suggest that psychological distress, social isolation, lack of company, and worrying during the COVID-19 pandemic were highly prevalent in youth and, interestingly, associated with the current use of, and a positive attitude toward, digital interventions [33]. the current study, we use EMA items that have been previously used and validated to measure moment-to-moment variation in stress/negative affect, with considerable within-person variability having been observed for these items in several EMA studies [43,95,121] , interindividual differences in within-person variability as well as general response tendencies may influence the number of triggered EMI tasks and, hence, further research is needed to optimize and personalize the assignment of EMI components, e.g., by using methods of artificial intelligence, recurrent neural networks (RNNs) in particular [122].…”
Section: Discussionmentioning
confidence: 99%
“…the current study, we use EMA items that have been previously used and validated to measure moment-to-moment variation in stress/negative affect, with considerable within-person variability having been observed for these items in several EMA studies [43,95,121] , interindividual differences in within-person variability as well as general response tendencies may influence the number of triggered EMI tasks and, hence, further research is needed to optimize and personalize the assignment of EMI components, e.g., by using methods of artificial intelligence, recurrent neural networks (RNNs) in particular [122]. So for example, we currently aim to apply RNNs in an ongoing study personalized digital mental health promotion and prevention in youth [33]. In addition, clinical staging models of severe mental disorder require further scrutiny, including heterogeneity in phenomenology, course and outcome within individual stages [5,123,124].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lockdown decreased environmental exposures and the incidence of seasonal infections [8,9]. Moreover, protracted and forced home-stay may have risen the accesses in the PED for functional affections, especially in adolescents [10].…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…The vast majority of Americans across age, race/ethnicity, and socioeconomic status own smartphones; and of those, most use mobile apps [32,33]. Several studies have shown that people experiencing stress are more likely to use meditation apps (eg, Calm) [34][35][36][37]. Using a simple mHealth app to deliver guided imagery audio files has the potential for simulating outdoor experiences for people experiencing lockdowns and social isolation, as well as for individuals who are homebound due to other reasons.…”
Section: Introductionmentioning
confidence: 99%